PENGARUH KEPEMIMPINAN TRANSFORMATIF, DAN LOCUS OF CONTROL TERHADAP KINERJA ORGANISASI SMK BINTANG NUSANTARA SCHOOL - Dakun, Dakun (Jurnal Inovasi dan Teknologi Pendidikan, 2023)
Leaders need to build skills and knowledge to overcome challenges and developments in information technology in the era of the industrial revolution 4.0. Technology skills, creativity, and risk management need to be understood and mastered by leaders. Transformative leaders can increase employee satisfaction and psychological well-being which has an impact on organizational productivity and performance. Locus of control motivates individuals to solve problems and adapt to change. This study aims to determine the effect of transformative leadership and locus of control on organizational performance. This research is quantitative. Respondents in this study were parents of students at SMK Bintang Nusantara School. The results of the study show that the transformative leadership of the principal at SMK Bintang Nusantara School has an impact on a more conducive work situation and locus of control owned by educators and education staff to provide satisfaction to parents of students so that it directly affects organizational performance